PERKEMBANGAN LIBERALISASI INVESTASI DARI ASEAN FRAMEWORK AGREEMENT ON SERVICES (AFAS) PAKET 1 SAMPAI PAKET 8 DAN MASUKNYA FOREIGN DIRECT INVESTMENT (FDI) ASAL ASEAN PADA JASA TRANSPORTASI UDARA INDONESIA - H Herlitah (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2016)
This paper aims to explain how about the level of commitment of Indonesia in air transport services in cooperation AFAS Package 1- 8 and the development of investment in this sector since the signing of the cooperation AFAS Package 1 - 8. To map the position of Indonesia in the sector of air transport services in cooperation AFAS the method used were indexation and Hoekman index. To measure competitiveness using Data Envelopment Analysis (DEA) to measure the economic impact analysis of input-output model of regional ASEAN. Based on the analysis of AFAS 1-8 shows that the air transport services sector until now has not been opened. Domestic liberalization conditions under Regulation Updates (DNI 2016) FEP allowed on air transport services between 49 percent to 67 percent. One of the sub-sectors that have been opened with the majority shareholding for foreigners (67 per cent) is supporting air transport services subsector. When seen through the analysis of the competitiveness of efficient transport services based on the value of the Indonesia Air Transport efficient only remaining other services are still very much value for efficient.